2014
DOI: 10.1504/ijmp.2014.060540
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the recession on the quality of working life of UK managers: an empirical study

Abstract: This paper explores the effect of the post-2007 recession on UK managers using a unique data set derived from the Quality of Working Life Project. This project has been running since 1997 in partnership with UK's Chartered Management Institute. The paper compares a wide range of measures from surveys run in 2007 (immediately before the 'credit crunch') and in 2012 as the UK was slowly emerging from the recession. Data from the surveys are used to examine the extent, pace and nature of organisational change, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 19 publications
4
25
0
1
Order By: Relevance
“…Indeed, we concur with scholars who call for innovative empirical insights into the ‘lived experience’ of managers that are neither hampered by the imposition of existing categorizations (see Korica, Nicolini and Johnson, ; Mintzberg, ) nor restricted by theoretical insights that are disconnected from empirical understanding (see Hales, ). Thus, building on the recent work of Worrall and Cooper (, ), and consistent with calls from scholars such as Korica, Nicolini and Johnson () and Tengblad (), we argue that central to understanding managerial work should be uncovering the reflections of the same managers to events around them and analysing these over time. We document and analyse the reflections of middle managers on their own actions and behaviours in relation to changes that may be linked to the recession, but also to developments resulting from the choices of executives in imposing particular regimes and extending austerity measures.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Indeed, we concur with scholars who call for innovative empirical insights into the ‘lived experience’ of managers that are neither hampered by the imposition of existing categorizations (see Korica, Nicolini and Johnson, ; Mintzberg, ) nor restricted by theoretical insights that are disconnected from empirical understanding (see Hales, ). Thus, building on the recent work of Worrall and Cooper (, ), and consistent with calls from scholars such as Korica, Nicolini and Johnson () and Tengblad (), we argue that central to understanding managerial work should be uncovering the reflections of the same managers to events around them and analysing these over time. We document and analyse the reflections of middle managers on their own actions and behaviours in relation to changes that may be linked to the recession, but also to developments resulting from the choices of executives in imposing particular regimes and extending austerity measures.…”
Section: Introductionsupporting
confidence: 69%
“…A potentially complicating factor in understanding the dynamics in managerial work is the impact of extreme economic stressors such as recession and austerity. However, although some scholars have identified the generally destructive forces of economic recessions (see Hassard, Morris and McCann, ; Worrall and Cooper, , ), few have provided extended empirical analyses of managerial reflections regarding these implications. In the context of existing and ongoing transformations, the recent economic recession and the ensuing austerity choices (in many advanced economies, but especially in the UK for the purposes of this paper) have added a new dynamic to studying managerial work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature further indicates that factors such as job satisfaction, employee well-being, perceived stress and working conditions are integral to the construct 'Quality of Work Life' (QWL), through varied conceptualizations of the construct given over the years (e.g., Warr, Cook & Wall, 1979;Harrison, 1985;Loscocco & Roschelle, 1991;Worrall, et al, 2016). According to Martel & Dupius (2006), Quality of Work Life, at a given time, corresponds to a condition experienced by the individual in his or her dynamic pursuit of his or her hierarchically organized goals within work domains where the reduction of the gap separating the individual from these goals is reflected by a positive impact on the individual's general quality of life, organizational performance, and consequently the overall functioning of the society (p.355).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…If that is the case, then one would expect to find older managers and professionals losing their privileged position and affected just like in other occupations by more pressure and tighter monitoring, while no longer able to extract class 'rents' (Sørensen, 2000) through deferred compensation and benefits. 4 The increased use of financial incentives for managers and professionals, noted above, surely indicates a greater emphasis on short-term performance, while the study of Worrall and Cooper (2001) showed managers in particular under considerable strain from continuous organizational change. This view has been countered however by arguments that employers have limited scope for changing the established treatment of the service class.…”
Section: Class Concepts In Relation To Older Employeesmentioning
confidence: 99%